FREQUENCY OF ABO AND RH (D) BLOOD GROUPS INVOLVING VOLUNTEER DONORS IN DISTRICT NOWSHERA - Khan, Bilal Hassan; Attaullah, Shahnaz; Khan, Awais Hassan (Journal of Postgraduate Medical Institute, 2017)
Objective: To find out the frequency of ABO and Rh (D) blood groups among healthy volunteer blood donors in District Nowshera. Methodology: This descriptive cross sectional study was conducted from April, 2015 to March, 2016 in District Nowshera. Blood group of 1190 healthy college's students who wanted to donate blood were analyzed while data of 2410 blood donors were collected from Civil Hospital, Pabbi and District Hospital Nowshera. The data of total study subjects (3600) were analyzed following standard statistical procedures. Results: Out of 3600 healthy adult donors, males were 2580 and females were 1020, with a male to female ratio of 2.52:1. Group "˜B' (32.0 %) was found to be most predominant blood group, followed by "O" (29.8%), "A" (27.4 %) and "AB" groups were (10.8 %). Rh (D) was found to be positive in 3348 (93%) subjects in the study population. Conclusion: Blood group "˜B' had the maximum frequency and "AB" had the minimum occurrence among blood donors of District Nowshera. Majority of blood groups were Rh (D) positive.